Integrated Cr and S poisoning of a La0.6Sr0.4Co0.2Fe0.8O3−δ (LSCF) cathode for solid oxide fuel cells. Issue 1 (22nd December 2020) - Wang, Cheng Cheng; Gholizadeh, Mortaza; Hou, Bingxue; Fan, Xincan
Abstract : Strontium segregation in a La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ (LSCF) electrode reacts with Cr and S in a solid oxide fuel cell (SOFC), which can cause cell performance deterioration. Abstract : Strontium segregation in a La0.6 Sr0.4 Co0.2 Fe0.8 O3− δ (LSCF) electrode reacts with Cr and S in a solid oxide fuel cell (SOFC), which can cause cell performance deterioration. Integrated Cr and S poisoning for LSCF cathodes of SOFC was studied at 800 °C of 200 mA cm −2 (cathodic) for 20 h. After polarization in Cr and S at 800 °C for 20 h, polarization and ohmic resistances for LSCF were 2.4 Ω cm 2 and 3.4 Ω cm 2, which were larger than those for LSCF electrodes after Cr deposition only and S deposition only, respectively. The results illustrated that Cr and S deposition occurred on the surface of LSCF, which could form SrCrO4 and SrSO4 . Compared to Cr deposition only and S deposition only, integrated Cr and S deposition was unsystematic, and the degradation phenomenon of Cr and S poisoning was more severe. The integrated Cr and S deposition of the LSCF electrodes was induced via interactions among CrO, SO2 and segregated SrO from LSCF.